2023
DOI: 10.1097/sla.0000000000005940
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and NETosis Modulation in Traumatic Heterotopic Ossification

Abstract: Objective: To characterize the role of neutrophil extracellular traps (NETs) in heterotopic ossification (HO) formation and progression and to use mechanical and pharmacological methods to decrease NETosis and mitigate HO formation. Background: Traumatic HO is the aberrant osteochondral differentiation of mesenchymal progenitor cells after traumatic injury, burns, or surgery. While the innate immune response has been shown to be necessary for HO formation, the specific immune cell phenotype and function remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…When nearing the end of their lifespan, neutrophils typically cycle back to the bone marrow for turnover through the concomitant downregulation of CXCR2 and upregulation of CXCR4 ( 13 ). While some neutrophils are likely to terminate within the injury tissue through the formation of neutrophil extracellular traps (NETs) ( 31 , 32 ), a portion of neutrophils may cycle back to the bone marrow following homing to sites of injury. Expression analysis of Cxcr2 and Cxcr4 in our neutrophil population from the marrow, blood, and injury site showed the expected changes in receptor expression ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…When nearing the end of their lifespan, neutrophils typically cycle back to the bone marrow for turnover through the concomitant downregulation of CXCR2 and upregulation of CXCR4 ( 13 ). While some neutrophils are likely to terminate within the injury tissue through the formation of neutrophil extracellular traps (NETs) ( 31 , 32 ), a portion of neutrophils may cycle back to the bone marrow following homing to sites of injury. Expression analysis of Cxcr2 and Cxcr4 in our neutrophil population from the marrow, blood, and injury site showed the expected changes in receptor expression ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner to FOP, tHO has shown to be at least in part driven by inflammatory processes, many of which overlap with FOP inflammatory mechanisms. Like FOP patients, individuals with tHO have shown evidence of increased immune cell presence as well as increased inflammatory cytokines such as IL-3, IL-6, IL-10, and MCP-1 following blast and penetrating combat injuries [ 184 , 185 , 186 , 187 ]. Burn/tenotomy HO mouse models have also shown early increased levels of IL-6 and IL-1α in mice that form HO [ 187 ].…”
Section: Inflammatory Control Of Homentioning
confidence: 99%
“…Like FOP patients, individuals with tHO have shown evidence of increased immune cell presence as well as increased inflammatory cytokines such as IL-3, IL-6, IL-10, and MCP-1 following blast and penetrating combat injuries [ 184 , 185 , 186 , 187 ]. Burn/tenotomy HO mouse models have also shown early increased levels of IL-6 and IL-1α in mice that form HO [ 187 ]. Recent studies have shown that the NF-κB signaling pathway plays an important role in tHO; when the NF-κB cascade was blocked, HO formation significantly decreased [ 188 ].…”
Section: Inflammatory Control Of Homentioning
confidence: 99%
“…TGF-β produced by immune cells in HO exacerbates the disease, by inducing MSC migration and osteogenic differentiation ( MAO et al, 2020 ). Recent studies have shown that neutrophils are involved in HO injury and that toll-like receptor signaling is highly expressed in cells at the site of injury ( NUNEZ et al, 2023 ). Toll-like receptor signaling regulates BMSC function ( NEMETH et al, 2010 ).…”
Section: Cellular Interaction Of Immune Cells and Stem Cells In Jaw D...mentioning
confidence: 99%